Determination of Home Purchase Decisions with Technology Adoption as a Moderating Variable - Wati, Nurul Linda; Otok, Bambang Widjanarko (Research Horizon, 2025)
The residential property market in Indonesia has experienced significant growth, with a 1.89% increase in the Residential Property Price Index and a 31.16% rise in sales in the first quarter of 2024, though Surabaya recorded the lowest price growth in Java at 0.34%. This study aims to examine the determinants of home purchase decisions, including purchasing power, price, location, marketing advertisements, and developer brand image, with technology adoption as a moderating variable. Using a quantitative approach, data were collected from 225 respondents across four housing projects in Gresik, East Java, through questionnaires analyzed with Moderated Structural Equation Modeling. The findings reveal that all determinants significantly influence home purchase decisions, with developer brand image having the strongest effect. Technology adoption enhances these relationships by improving information access and consumer trust through digital platforms. The study concludes that developers should prioritize digital marketing strategies, such as virtual tours and social media campaigns, to boost consumer engagement and address declining sales trends. These insights offer strategic guidance for enhancing marketing effectiveness in the evolving digital landscape of the housing sector.